OPTIMASI PENGUMPULAN DAN PENGANGKUTAN SAMPAH KOTA DENGAN MENGGUNAKAN MODEL POWERSIM - M. Arief Budihardjo; Badrus Zaman (Diponegoro University, 2012)
Gathering and transportation of garbage represent problems in Town Semarang with 1.431.105 population. Neededan effort of effective garbage management breakthrough in order to improving efficiency and optimalisationgathering and transportation of garbage by using Powersim dynamic model. Powersim is windows base software tocreate the model of dynamic system with a simulator desain. Simulation of gathering and transportation garbagemodel in Town Semarang of early compilation concept. Compilation concept conducted by determining elementwhich playing a part in gathering and transportation process of garbage which interact and have depending.Concept formed to be formulated by as model which is the in form of the breakdown of, picture or formula. Here inafter simulation conducted with the model which have been made by including data to know behavior process of thegarbage gathering and transportation. Data input for the gathering to cover the garbage volume, appliancetransport the garbage and to the transportation of its data input cover the garbage volume in place Dismissal ofWhereas and appliance garbage transport. Result of research shown existing condition of garbage gathering andtransportation in Town Semarang not yet optimal, seen by garbage amount which not yet been transported byduring gathering process. After optimation proven by that any garbage transported at process of gathering andtransportation and also do not rest of garbage which piled up. For repair of gathering and transportationrecommended by gathering process (1) used a garbage pedicab amount to 1300 with 0,82 m2 capacity, 2 timesritation and operate everyday and ( 2) 15 dump truck, with 6 m3 capacity, 1 times rotation and operate everyday. Itstransportation repair used by arm roll truck as much 60 by 6 times ritation and have 6 m 3 capacities operatingeveryday